SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN DOSEN BERPRESTASI TINGKAT KOPERTIS WILAYAH I DENGAN METODE ELECTRE BERBASIS WEB - Pandi Barita Nauli Simangunsong; Sony Bahagia Sinaga (LPPM Politeknik LP3I Medan, 2019)
Determination of outstanding lecturers is useful to improve the quality of knowledge for a lecturer, the selection of lecturers who are competent in the results obtained can improve the quality of learning. The lack of knowledge of a lecturer is caused by the lack of care from a lecturer in developing a career so that the lecturer does not have competence in his career. The absence of selection of lecturers who excel at the national or university level makes lecturers minimal in developing their knowledge. The selection of lecturers who have achievements is very useful to improve the ability of lecturers to develop knowledge in achievement. The existence of criteria in the selection of outstanding lecturers can be applied by utilizing the electre method in producing criteria in determining outstanding lecturers. Based on the selection of outstanding lecturers that have been done from the many lecturers who participated in only one lecturer who was entitled to receive an award as an outstanding lecturer.